A new species of Olethreutes Hübner, 1822 (Lepidoptera, Tortricidae, Olethreutinae) from Korea - Kim, Jeong-Nam; Bayarsaikhan, Ulziijargal; Lee, Tak-Gi; Cha, Yeong-Bin; Kim, Hanul; Byun, Bong-Kyu; Bae, Yang-Seop (Zootaxa, 2022)
One new species of Olethreutes Hübner, 1822 species, O. oculata Kim, Byun & Bae, sp. nov., is described, and two related species, O. captiosana (Falkovitsh, 1960) and O. subtilana (Falkovitsh, 1959), are redescribed from Korea. Color figures of adults and images of genitalia are provided. [Zoobank registrations: Olethreutes oculata Kim, Byun & Bae, new species: LSID: urn:lsid:zoobank.org:act:814E618C-C13D-4FAC-A669-C3AD8673227F].